PEMAHAMAN UMAT TENTANG KEHADIRAN KRISTUS DALAM PERAYAAN EKARISTI DI PAROKI SANTA MARIA BLITAR - Andriani, Katarina Dian; Ardijanto, Don Bosco Karnan (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2021)
The purpose of this research is to explain the presence of Christ in the Eucharistic Celebration and the understanding of the Santa Maria Rejoso church stage of Santa Maria Parish Blitar about the presence of Christ in the Eucharistic Celebration. This research uses qualitative research methods with data collection techniques through interviews. The technique of selecting informants is using purposive sampling technique. The criteria of the informants are church stage’s managers and activists from the categorical group representatives. This research results are first, the people have understood the presence of Christ in their daily life, the two people understand that the Eucharist is a holy communion, the three people understand that Christ is present at the Eucharist, and the four the people believe that Christ doesn’t only present in the Eucharist celebration, but also in the other Liturgical celebration and in their daily life.